LncRNA RP11-686D22.10 is related with the survival of breast cancer patients, affects the proliferation, invasion of breast cancer cell lines - TANG Yijun, WANG Wenlong, LI Jiangli, YANG Huan, SUN Jing (Jichu yixue yu linchuang, 2023)
Objective To dientify the correlation between the expression of long-chain non-coding RNA (lncRNA) RP11-686D22.10 and the survival of breast cancer patients, and to explore the effect of over-expression of RP11-686D22.10 on the proliferation and invasion of breast cancer cell lines. Methods The relationship between the expression level of RP11-686D22.10 and the survival time of breast cancer patients was analyzed with GEPIA database. The expression of RP11-686D22.10 in mammary epithelial cell line MCF-10A and breast cancer cell lines MCF7, SKBR3, HCC1937, BT549 and MB-MDA-468 was detected by real-time quantitative polymerase chain reaction (RT-qPCR). SKBR3 cell with the least expression of RP11-686D22.10 was selected and transfected with control plasmid (NC group) and RP11-686D22.10 over-expression plasmid (RP11-686D22.10 group). The proliferation and invasion of breast cancer cells were detected by CCK-8 and Transwell assays, respectively. The Linc2Go database predicted the targeting microRNA (miRNA) of RP11-686D22.10, and the dual-luciferase reporter gene assay was used to target at relationship between RP11-686D22.10 and miR-454-3p. The expression of miR-454-3p was detected by RT-qPCR. Western blot was used to detect the protein expression of Wnt/β-catenin signaling pathway. Results Compared with breast cancer patients with low expression of RP11-686D22.10, patients with high expression of RP11-686D22.10 had longer overall survival (PConclusions The expression level of RP11-686D22.10 is closely related to the survival of breast cancer patients. Over-expression of RP11-686D22.10 inhibits the proliferation and invasion of breast cancer cell lines by targeting at miR-454-3p.